Jurnal Ilmu Komunikasi Yul Yanti: (STUDI DESKRIPTIF KUALITATIF PADA PENGGEMAR RED VELVET DAN PENGGEMAR BLACKPINK) - Yanti, Yul; Ginting, Eraskaita; Farid, M. Mifta (Jurnal Prodi Ilmu Komunikasi, 2024)
This research aims to find out how the group communication process on social media, with a focus on K-Pop fan groups Red Velvet and Blackpink on Twitter. The use of social media as a means of group communication has experienced rapid growth in recent years. This research uses a qualitative approach by analyzing the interacting accounts as well as a descriptive approach to get results that match the findings. The research method involved participant observation. Data was collected from a political Red Velvet and Blackpink community group consisting of 11 active members on Twitter. Various main aspects to be exploited in this research are group communication such as communication process, communication formation, communication style, and factors that influence the two communities to support each other so that they have differences from the group. The results of this study show that the group communication process of the Red Velvet and Blackpink communities on social media tends to be dynamic. It was found that each group member has a tendency to support other communities based on factors and their liking for the group itself. In addition, community members also consistently overcome cultural differences to avoid barriers and build significant friendship relationships. thus making these two communities have a big difference compared to other communities. This research provides a better understanding of group communication dynamics on social media, particularly in the context of Kpop fan group communication on Twitter. The findings have important implications in understanding how relationships and information are formed, addressing public opinion, as well as the implementation that K-pop fans should apply in the future.Keywords: group communication, Twitter, K-pop fans